Pembuktian Tindakan Pelecehan Seksual Verbal (Catcalling) dalam Perspektif Hukum Acara Pidana - Wulandari, Kadek Ayu; Sugama, I Dewa Gede Dana (Ethics and Law Journal: Business and Notary, 2025)
The study's objective is to examine the evidence that can be used to prove cases of crimes revealed verbally in the criminal process. The normative research method used in this research focuses on literature reviews such as books, articles in scientific journals, explaining the applicable rules and regulations verbally. In this research, the author implemented legal product design by researching various types of legal provisions, especially regulations in the Criminal Code and Criminal Procedure Code. The results of the research show that verbal sexual understanding (catcalling) in everyday life still often occurs because there is normalization and patriarchal culture and a lack of public knowledge about verbal sexual disclosure. Everyone, both those directly affected and those who observe it, must have the courage to report acts of disclosing sexual verbal acts so that the public will be more alert and avoid worse criminal legal action. Reports on understanding verbal sexuality should be adjusted to evidence that can be accounted for based on Article 184 of the Criminal Procedure Code. The application of evidence that can be accounted for in accordance with the Criminal Procedure Law in catcalling cases can be in the form of witness statements, video recordings and screenshot evidence of comments that indicate verbal sexual disclosure. Key Words: Verbal Sexual Harassment, Evidence, Criminal Procedure Law. Abstrak Tujuan dari penelitian ini adalah untuk mengkaji alat bukti untuk dapat digunakan dalam pembuktian kasus kejahatan pelecehan seksual verbal dalam proses peradilan pidana. Metode penelitian normatif yang digunakan dalam penelitian ini yang berfokus terhadap kajian pustaka seperti buku-buku, artikel pada jurnal ilmiah peraturan dan ketentuan yang berlaku pelecehan seksual verbal. Dalam penelitian ini, penulis mengimplementasikan perancangan produk hukum dengan cara meneliti mengenai berbagai jenis ketentuan UU terutama peraturan dalam KUHP dan KUHAP. Hasil studi menunjukkan bahwa pemahaman seksual verbal (catcalling) dalam sehari-hari masih sering terjadi karena terdapat normalisasi serta budaya patriarki dan kurangnya pengetahuan masyarakat akan pelecehan seksual verbal. Setiap orang baik pihak yang terkena dampak langsung maupun pihak yang mengamatinya harus berani melaporkan tindakan pelecehan seksual verbal agar masyarakat lebih waspada dan menghindari terjadinya tindak hukum kejahatan yang lebih buruk. Laporan pelecehan seksual verbal sebaiknya disesuaikan dengan alat bukti yang dapat dipertanggungjawabkan berdasarkan Pasal 184 KUHAP. Penerapan alat bukti yang dapat dipertanggungjawabkan sesuai dengan Hukum Acara Pidana terhadap kasus catcalling dapat berupa keterangan saksi, rekaman video dan bukti screenshot dari komentar yang berindikasi pelecehan seksual verbal. Kata Kunci: Pelecehan Seksual Verbal, Alat Bukti, Hukum Acara Pidana.